The Effects of Maximum Aerobic Capacity and Ratings of Perceived Exertion on Muscular Strength and Endurance - Zahra Ordudari; Ehsanollah Habibi (Iranian Journal of Health, Safety and Environment, 2019)
Grip and pinch strength are the most important factors affecting the hand's performance. This study aimed to evaluate the relationship among maximum aerobic capacity (Vo2max) and ratings of perceived exertion (RPE) with grip and pinch strength and endurance and their impact on these factors. This cross-sectional study was performed among 83 male students and office workers by means of simple random sampling. To assess the Vo2max, RPE, grip and pinch strength and endurance the Step Test, Borg scale, dynamometer and pinch gauge were used, respectively. The findings of the study indicate that there is a direct relationship between the Vo2max with grip strength and endurance, pinch strength and endurance and BMI. On the other hand, there is an indirect relationship between RPE with grip and pinch strength and Vo2max. Moreover, there was no relationship between RPE with grip and pinch endurance. It was also found that there is a direct relationship between the BMI with grip and pinch strength, pinch endurance, and Vo2max. Finally, no relationship was observed between BMI and grip endurance. Moreover, the Vo2max was found to have no influence on the grip and pinch strength and pinch endurance, but it has an influence on the grip endurance. In jobs that require high grip and pinch strength and endurance employed those with high Vo2max so that work-related musculoskeletal disorders (WMSDs) would be prevented.